A negative electrode additive for high temperature resistant energy storage battery

By using composite additives in the negative electrode of lead-acid battery, including barium sulfate, carbon black, sodium ligninsulfonate, humic acid, sodium polyacrylate and block copolymer, the negative electrode additives have poor high temperature tolerance at extreme temperatures. Problem, better low temperature performance and stronger high temperature tolerance are achieved.

CN118867252BActive Publication Date: 2025-02-07ZHEJIANG EDENDA NEW ENERGY MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411350695.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-02-07
Estimated Expiration
2044-09-26

AI Technical Summary

Technical Problem

Existing lead-acid battery negative electrode additives show poor high temperature tolerance at extreme temperatures, resulting in a decrease in low temperature discharge performance and cannot meet the application needs in wide temperature zones.

Method used

Using a composite negative electrode additive, including barium sulfate, carbon black, sodium ligninsulfonate, humic acid, sodium polyacrylate and block copolymer, the physical or chemical adsorption force of the expansion agent and lead paste is enhanced through these components. Form a highly hydrophilic gel zone to improve the ion diffusion rate and metal ion complexing ability.

Benefits of technology

It significantly improves the low-temperature discharge performance and high-temperature tolerance of lead-acid batteries, and expands its application field in wide temperature zones.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118867252B_ABST
    Figure CN118867252B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of negative electrode additives for energy storage batteries, and in particular to a negative electrode additive for a high temperature resistant energy storage battery. The additive comprises the following raw materials by weight: 0.8-1.25 parts of barium sulfate, 0.15-0.35 parts of carbon black, 0.1-0.3 parts of sodium lignin sulfonate, 0.2-0.4 parts of humic acid, 0.01-0.05 parts of sodium polyacrylate, and 0.05-0.15 parts of a block copolymer. The invention uses barium sulfate, carbon black, sodium lignin sulfonate, humic acid, sodium polyacrylate and a block copolymer of sodium polypropylene sulfonate to form a composite additive for the negative electrode of a lead-acid battery. The composite additive used in the invention is matched with sodium polyacrylate with high hydrophilicity under the existing additive system to form a gel area on the surface of lead, has high "liquid retention" ability in both high temperature and severe cold climates, improves ion diffusion rate, balances changes in local electrolyte density, and can provide a function of capturing metal ions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of negative electrode additives for energy storage batteries, and in particular to a negative electrode additive for high temperature resistant energy storage batteries. Background Art

[0002] Lead-acid batteries in energy storage batteries are still the preferred power solution in many fields due to their mature technology, low cost, high safety, good environmental adaptability and simple maintenance. With the rapid development of energy technology, higher requirements are also placed on the performance of lead-acid batteries. One of the main challenges is to maintain high discharge capacity in a wide temperature range of -20~50℃, especially in low temperature environments. Generally, as the temperature decreases, the internal resistance of lead-acid batteries increases, and their discharge performance is mainly limited by the negative electrode.

[0003] The active material of the negative electrode is fine-wool sponge lead, which has the characteristics of high porosity and large surface area. Due to the high surface energy of the material, there is a tendency to decrease spontaneously, so that the sponge lead particles continue to aggregate and grow during the charge and discharge process, and finally the active material of the negative plate shows a "shrinkage" phenomenon, that is, the porosity continues to decrease and the utilization rate decreases. In addition, the battery discharge performance is also affected by the concentration polarization of the sulfuric acid electrolyte. Due to the slow ion diffusion rate, a large amount of lead sulfate is enriched on the surface of the negative electrode, and even a dense lead sulfate "passivation layer" is formed, which hinders the reaction between lead and electrolyte, and finally the negative electrode discharge capacity drops sharply.

[0004] In current technology, by adding additives such as sodium lignin sulfonate, barium sulfate and carbon black, commonly known as "expanders", to the negative electrode, the "shrinkage" and "passivation" of the active material can be effectively inhibited. However, the current expanders still cannot meet the performance requirements of lead-acid batteries at extreme temperatures, especially after the battery is charged and discharged in a high temperature environment (i.e., the battery's formation reaction), which seriously affects the low-temperature discharge performance. The reason is that the expander has poor high-temperature tolerance, and the increase in the temperature inside the battery accelerates the molecular movement. This change destroys the initial tight combination of the expander and the lead active material.

[0005] Therefore, the present invention aims to provide a negative electrode additive that is resistant to high temperatures and is used to inhibit the "shrinkage" and "passivation" of active materials in lead-acid energy storage batteries. Summary of the invention

[0006] In view of the above problems in practical applications of lead-acid batteries and the limitations of the prior art, the present invention aims to provide a negative electrode additive for high-temperature resistant energy storage batteries, which is used to enhance the physical or chemical adsorption force between the expander and the lead paste, improve the low-temperature performance of the lead-acid battery, and expand its application field in a wide temperature range.

[0007] To achieve the above object, the present invention provides the following technical solutions:

[0008] The present invention provides a negative electrode additive for a high temperature resistant energy storage battery, wherein the additive comprises the following raw materials in parts by weight:

[0009] 0.8-1.25 parts of barium sulfate, 0.15-0.35 parts of carbon black, 0.1-0.3 parts of sodium lignin sulfonate, 0.2-0.4 parts of humic acid, 0.01-0.05 parts of sodium polyacrylate, and 0.05-0.15 parts of block copolymer.

[0010] Preferably, the additive comprises the following raw materials by weight:

[0011] 1 part of barium sulfate, 0.3 parts of carbon black, 0.2 parts of sodium lignin sulfonate, 0.3 parts of humic acid, 0.025 parts of sodium polyacrylate, and 0.08 parts of block copolymer.

[0012] Preferably, the weight average molecular weight Mw of the sodium polyacrylate is 1000-8000.

[0013] As further preferred, the weight average molecular weight Mw of the sodium polyacrylate is 3000-6000.

[0014] Preferably, the block copolymer is one or more of polybutene dicarboxylic acid-polyacrylic acid diblock (AB salt diblock), polybutene dicarboxylic acid-polyacrylic acid sulfonate diblock (AC salt diblock), polyacrylic acid-polyacrylic acid sulfonate diblock (BC salt diblock), and polybutene dicarboxylic acid-polyacrylic acid sulfonate triblock (ABC salt triblock).

[0015] In addition, further, the block copolymer is preferably one or more of polybutene dicarboxylic acid-polypropylene sulfonate diblock (AC salt diblock), polyacrylic acid-polypropylene sulfonate diblock (BC salt diblock), and polybutene dicarboxylic acid-polyacrylic acid-polypropylene sulfonate triblock (ABC salt triblock).

[0016] Preferably, the ratio of each homopolymer in the block copolymer is 0.3-0.7:1, the weight average molecular weight Mw of each homopolymer is 500-2000, and the weight average molecular weight of the block copolymer is 8000-30000.

[0017] Furthermore, more preferably, the ratio of each homopolymer in the block copolymer A:B, A:C, B:C or (A+B):C is 0.5:1, the weight average molecular weight Mw of each homopolymer is 600-1200, and the Mw of the block copolymer is 10000-20000.

[0018] Preferably, the block copolymer is one or more of sodium salt, potassium salt, calcium salt or barium salt block copolymers, more preferably one or two of sodium salt and potassium salt block copolymers.

[0019] Preferably, the block copolymer is a polybutene dicarboxylic acid-polypropylene sulfonic acid sodium salt diblock, the ratio of sodium polybutene dicarboxylate:sodium polypropylene sulfonate is 0.5:1, the Mw of sodium polybutene dicarboxylate is 600-1000, the Mw of sodium polypropylene sulfonate is 800-1200, and the Mw of polybutene dicarboxylic acid-polypropylene sulfonic acid sodium salt diblock is 12000-16000.

[0020] The beneficial effects of the present invention are:

[0021] (1) The present invention aims to solve the problem of a sharp drop in low-temperature capacity of lead-acid batteries after operation in extremely high or low temperature environments and the disadvantage of poor high-temperature tolerance of existing expanders. The present invention uses barium sulfate, carbon black, sodium lignin sulfonate, humic acid, sodium polyacrylate and sodium polypropylene sulfonate block copolymer to form a composite additive for the negative electrode of a lead-acid battery. The composite additive used in the present invention is a highly hydrophilic sodium polyacrylate in the existing additive system to form a gel area on the lead surface. It has a high "liquid retention" ability in both high temperature and severe cold climates, improves the ion diffusion rate, balances the changes in local electrolyte density, and can also provide a function of capturing metal ions.

[0022] (2) The block copolymer introduced by the present invention is a water-swellable polymer containing a large number of hydrophilic carboxyl groups, and can be selectively embedded with sulfonate chain segments to form a flexible structure of a cross-linked network, which gives it high thermal stability, water absorption and strong metal ion complexing ability. The block copolymer of sodium polyacrylate and sodium polypropylene sulfonate not only enhances the surface activity of the additive, but also its network structure is "bound" together with barium sulfate, carbon black, sodium lignin sulfonate and humic acid through physical structural interweaving, entanglement or electrostatic action to form a uniformly dispersed and stable ion diffusion gel layer of organic / inorganic expander, so as to avoid direct contact between lead and electrolyte, greatly slow down the growth of lead sulfate layer, and finally achieve the effect of improving the high temperature tolerance and low temperature performance of the battery.

[0023] In summary, the negative electrode additive of the present invention can enable lead-acid energy storage batteries to have better low-temperature performance and stronger high-temperature tolerance, and is particularly suitable for the technical field of negative electrode additives for lead-acid energy storage batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a physical picture of the negative electrode additive of the present invention. DETAILED DESCRIPTION

[0025] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] In the description of the present invention, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as limiting the present invention.

[0027] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0028] Embodiment 1:

[0029] A negative electrode additive for high temperature resistant energy storage battery:

[0030] According to the weight of lead powder, accurately weigh 0.8 parts of barium sulfate, 0.15 parts of carbon black, 0.1 parts of sodium lignin sulfonate, 0.2 parts of humic acid, 0.01 parts of sodium polyacrylate, and 0.05 parts of polybutene dicarboxylic acid-polypropylene sulfonate barium salt diblock; wherein the Mw of sodium polyacrylate is 1000, the A:C of polybutene dicarboxylic acid-polypropylene sulfonate barium salt diblock (AC barium salt diblock) is 0.3:1, the Mw of A and C is 500, and the Mw of polybutene dicarboxylic acid-polypropylene sulfonate barium salt diblock is 8000.

[0031] Embodiment 2:

[0032] A negative electrode additive for high temperature resistant energy storage battery:

[0033] 1.25 parts of barium sulfate, 0.35 parts of carbon black, 0.3 parts of sodium lignin sulfonate, 0.4 parts of humic acid, 0.05 parts of sodium polyacrylate, 0.15 parts of polybutene dicarboxylic acid-polypropylene sulfonic acid calcium salt diblock, wherein the Mw of sodium polyacrylate is 8000, the A:C of polybutene dicarboxylic acid-polypropylene sulfonic acid calcium salt diblock (AC calcium salt diblock) is 0.7:1, the Mw of A and C is 2000, and the Mw of polybutene dicarboxylic acid-polypropylene sulfonic acid calcium salt diblock is 30000.

[0034] Embodiment 3:

[0035] A negative electrode additive for high temperature resistant energy storage battery:

[0036] 1 part of barium sulfate, 0.3 parts of carbon black, 0.2 parts of sodium lignin sulfonate, 0.3 parts of humic acid, 0.025 parts of sodium polyacrylate, 0.08 parts of polybutene dicarboxylic acid-polypropylene sulfonic acid sodium salt diblock, wherein the Mw of sodium polyacrylate is 4000, the A:C of polybutene dicarboxylic acid-polypropylene sulfonic acid sodium salt diblock (AC sodium salt diblock) is 0.5:1, the Mw of A and C is 900, and the Mw of polybutene dicarboxylic acid-polypropylene sulfonic acid sodium salt diblock is 15000.

[0037] Embodiment 4:

[0038] Same as Example 3, except that the block copolymer is a diblock of polybutene dicarboxylic acid-polypropylene sulfonate potassium salt (AC potassium salt diblock).

[0039] Embodiment 5-8:

[0040] Same as Example 1-4, except that the block copolymer is a polyacrylic acid-polypropylene sulfonate diblock (BC salt diblock), wherein Example 5 is a potassium salt block copolymer, Example 6 is a sodium salt block copolymer, Example 7 is a calcium salt block copolymer, and Example 8 is a barium salt block copolymer.

[0041] Embodiment 9-12:

[0042] Same as Example 1-4, except that the block copolymer is a triblock of polybutene dicarboxylic acid-polyacrylic acid-polypropylene sulfonate (ABC salt triblock), wherein Example 9 is a sodium salt block copolymer, Example 10 is a potassium salt block copolymer, Example 11 is a barium salt block copolymer, and Example 12 is a calcium salt block copolymer.

[0043] Embodiment 13-16:

[0044] Same as Example 1-4, but different from Example 1-4 in that the block copolymer is a polybutene dicarboxylic acid-polyacrylic acid diblock (AB salt diblock).

[0045] Embodiment 17:

[0046] Meanwhile, Example 3 is different from Example 3 in that the block copolymer is a mixture of polybutene dicarboxylic acid-polyacrylic acid diblock (AB salt diblock) and polybutene dicarboxylic acid-polypropylene sulfonic acid sodium salt diblock (AC sodium salt diblock).

[0047] Embodiment 18:

[0048] Meanwhile, Example 3 is different from Example 3 in that the block copolymer is a mixture of a polybutenedicarboxylic acid-polyacrylic acid diblock (AB salt diblock) and a block copolymer is a polyacrylic acid-polypropylene sulfonate diblock (BC salt diblock).

[0049] Embodiment 19:

[0050] Meanwhile, Example 3 is different from Example 3 in that the block copolymer is a mixture of polybutene dicarboxylic acid-polyacrylic acid sodium salt diblock (AB sodium salt diblock) and polybutene dicarboxylic acid-polyacrylic acid-polypropylene sulfonic acid sodium salt triblock (ABC sodium salt triblock).

[0051] Embodiment 20:

[0052] Meanwhile, Example 3 is different from Example 3 in that the block copolymer is a mixture of polybutene dicarboxylic acid-polypropylene sulfonic acid sodium salt diblock (AC sodium salt diblock) and polyacrylic acid-polypropylene sulfonic acid sodium salt diblock (BC sodium salt diblock).

[0053] Embodiment 21:

[0054] Meanwhile, Example 3 is different from Example 3 in that the block copolymer is a mixture of polybutene dicarboxylic acid-polypropylene sulfonic acid sodium salt diblock (AC sodium salt diblock) and polybutene dicarboxylic acid-polyacrylic acid-polypropylene sulfonic acid sodium salt triblock (ABC sodium salt triblock).

[0055] Embodiment 22:

[0056] Meanwhile, Example 3 is different from Example 3 in that the block copolymer is a mixture of polyacrylic acid-polypropylene sulfonic acid sodium salt diblock (BC sodium salt diblock) and polybutylene dicarboxylic acid-polyacrylic acid-polypropylene sulfonic acid sodium salt triblock (ABC sodium salt triblock).

[0057] Embodiment 23:

[0058] At the same time, Example 3 is different from Example 3 in that the block copolymer is a mixture of polybutene dicarboxylic acid-polyacrylic acid sodium salt diblock (AB sodium salt diblock), polybutene dicarboxylic acid-polypropylene sulfonic acid sodium salt diblock (AC sodium salt diblock) and polyacrylic acid-polypropylene sulfonic acid sodium salt diblock (BC sodium salt diblock).

[0059] Embodiment 24:

[0060] At the same time, Example 3 is different from Example 3 in that the block copolymer is a mixture of polybutene dicarboxylic acid-polyacrylic acid sodium salt diblock (AB sodium salt diblock), polybutene dicarboxylic acid-polypropylene sulfonic acid sodium salt diblock (AC sodium salt diblock) and polybutene dicarboxylic acid-polyacrylic acid-polypropylene sulfonic acid sodium salt triblock (ABC sodium salt triblock).

[0061] Embodiment 25:

[0062] At the same time, Example 3 is different from Example 3 in that the block copolymer is a mixture of polyacrylic acid-polypropylene sulfonic acid sodium salt diblock (BC sodium salt diblock), polybutene dicarboxylic acid-polypropylene sulfonic acid sodium salt diblock (AC sodium salt diblock) and polybutene dicarboxylic acid-polyacrylic acid-polypropylene sulfonic acid sodium salt triblock (ABC sodium salt triblock).

[0063] Comparative Examples 1-4:

[0064] Meanwhile, Example 1-4 is different from Example 1-4 in that the additive does not contain a block copolymer.

[0065] The additives in the above-mentioned Examples 1-25 and Comparative Examples 1-4 were added to the paste machine and mixed with lead powder, water and acid, and the lead paste was made according to the conventional process; the lead paste was coated on the board and solidified, and a 2V4Ah lead-acid battery was made according to the conventional process. In order to simulate the influence of high temperature environment on battery performance, the battery discharge performance and -18℃ low temperature discharge performance were tested under the conditions of 50℃ and room temperature (25℃) respectively. The test results of different embodiments and comparative examples are shown in Table 1 below.

[0066] In Table 1, the low-temperature capacity reduction rate is calculated as follows: (discharge capacity of a battery formed at 1-50°C at -18°C / discharge capacity of a battery formed at 25°C at -18°C) × 100%.

[0067] like Figure 1The physical picture of the negative electrode additive is shown. The difference between Examples 1-25 and Comparative Examples 1-4 is whether the block copolymer is added. By comparing the examples with the comparative examples, it can be seen that the low-temperature capacity decrease rate values ​​of the embodiments of the present invention are lower than those of the comparative examples, especially when the additive of Example 7 is added to the negative electrode lead paste of the prior art, its 2-hour rate discharge capacity at 25°C under high-temperature formation and room-temperature formation conditions exceeds the level of the comparative examples, and the low-temperature capacity of the battery after high-temperature formation is increased by more than 10% year-on-year, further indicating that the block copolymer of sodium polyacrylate and sodium polypropylene sulfonate can enhance the interaction between the expander and the lead surface, improve the high temperature resistance of the expander, and significantly improve the low-temperature discharge performance of the battery.

[0068] By comparing Examples 1-4, 5-8, and 9-12, it can be seen that among the same type of block copolymers, when block copolymers of barium salts, calcium salts, sodium salts and potassium salts are used as additives, the block copolymers of sodium salts and potassium salts have particularly obvious improvements in the high temperature tolerance of the negative electrode, and can effectively improve the low temperature capacity of the battery, and the effect is far better than the block copolymers of barium salts and calcium salts. By comparing Examples 2-3, it can be seen that a large amount of added block copolymers can significantly improve the high temperature tolerance of the negative electrode, but the cost is high, which is far less cost-effective than the method of using the sodium salt block copolymer of Example 3.

[0069] Through the group comparison of Examples 1-4, Examples 5-8, Examples 9-12 and Examples 13-16, it can be seen that when AB salt diblock, BC salt diblock, AC salt diblock and ABC salt triblock are used as additives in negative electrode materials, the improvement effects of the latter three are far superior to those of the former.

[0070] In addition, through the comparison of Examples 17 to 25, it can be seen that the AB salt diblock, BC salt diblock, AC salt diblock and ABC salt triblock can be mixed as additives to act on the negative electrode material, which can also significantly improve the high temperature tolerance of the negative electrode and effectively improve the low temperature capacity of the battery.

[0071] As described above, the present invention can enhance the high-temperature thermal stability of the negative electrode additive, improve the low-temperature discharge performance of the battery, and improve the applicability of the lead-acid battery in a wide temperature range.

[0072] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A negative electrode additive for a high temperature resistant lead-acid battery, characterized in that: The following raw materials are included by weight: 0.8-1.25 parts of barium sulfate, 0.15-0.35 parts of carbon black, 0.1-0.3 parts of sodium lignin sulfonate, 0.2-0.4 parts of humic acid, 0.01-0.05 parts of sodium polyacrylate and 0.05-0.15 parts of block copolymer, wherein the block copolymer is one or more of AB salt diblock, AC salt diblock, BC salt diblock and ABC salt triblock, A is polybutene dicarboxylic acid, B is polyacrylic acid, C is polypropylene sulfonic acid, and the block copolymer is one or more of sodium salt, potassium salt, calcium salt or barium salt block copolymer.

2. The negative electrode additive for a high temperature resistant lead-acid battery according to claim 1, characterized in that: The additives include the following raw materials by weight: 1 part of barium sulfate, 0.3 parts of carbon black, 0.2 parts of sodium lignin sulfonate, 0.3 parts of humic acid, 0.025 parts of sodium polyacrylate, and 0.08 parts of block copolymer.

3. A negative electrode additive for a high temperature resistant lead-acid battery according to claim 1, characterized in that: The weight average molecular weight Mw of the sodium polyacrylate is 1000-8000.

4. The negative electrode additive for a high temperature resistant lead-acid battery according to claim 3, characterized in that: The weight average molecular weight Mw of the sodium polyacrylate is 3000-6000.

5. The negative electrode additive for a high temperature resistant lead-acid battery according to claim 1, characterized in that: The ratio of each homopolymer in the block copolymer is A:C, B:C or (A+B):C is 0.3-0.7:1, the weight average molecular weight Mw of each homopolymer is 500-2000, and the weight average molecular weight of the block copolymer is 8000-30000.

6. The negative electrode additive for a high temperature resistant lead-acid battery according to claim 5, characterized in that: The ratio of each homopolymer in the block copolymer is A:C, B:C or (A+B):C is 0.5:1, the weight average molecular weight Mw of each homopolymer is 600-1200, and the Mw of the block copolymer is 10000-20000.

Citation Information

Patent Citations

  • Negative electrode lead paste of lead-carbon storage battery and preparation method of negative electrode lead paste

    CN116565159A

  • Bipolar plate, bipolar lead-acid battery and preparation method of bipolar lead-acid battery

    CN116565344A

  • Lead storage battery

    JP2015032481A